Interventional Therapy in Refractory Hypertension: An Update - Clement Alexandra; Tudurachi Bogdan; Benchea Laura; Sascău Radu A.; Stătescu Cristian (Sciendo, 2022)
Hypertension represents a major public health issue, affecting about 26% of the world's population. It is the most common cardiovascular risk factor worldwide, with a prevalence that continues to grow. Among this hypertensive population, a critical subgroup is that of patients with resistant hypertension. For subjects with truly resistant hypertension, the next step after nonpharmacological interventions and drug therapy is represented by interventional treatment. However, implementing an interventional approach in resistant hypertension represents a real challenge. The decision needs to be undertaken in multidisciplinary teams, which must include a specialist in hypertension, and it is not routinely recommended. The main device-based therapies for hypertension are represented by carotid baroreceptor stimulation, renal denervation, and the creation of an arteriovenous fistula. Until 2018, there was an important controversy on the beneficial effects of renal sympathetic denervation. One cannot ignore, however, the positive results of interventional therapy for treatment-resistant hypertension obtained in different trials conducted on a large number of patients. A significant reduction in blood pressure values and an improvement in cardiovascular outcomes could be attained with interventional therapy through a rigorous selection of patients.